Peningkatan Kemampuan Berpikir Anak Usia Dini Melalui Pendekatan Permainan Coding - Maesaroh Lubis; Elfan Fanhas Fatwa Khonaeny; Sarmidi Sarmidi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Young children today live in a modern age that is inseparable from technology. They can easily use electronic devices. Children’s technological skills in this modern era need to be harnessed and nurtured by developing their logical and creative thinking abilities, one of which is through coding. This study aims to gain a deeper understanding of how coding can enhance young children’s thinking skills. This study employs a literature review methodology. The findings indicate that coding enhances children’s thinking processes, encompassing creativity, imagination, logical reasoning, systematic thinking, critical thinking, and meticulousness when solving problems. The driving force behind coding education is computational thinking (CT). Coding and CT are closely interrelated. CT is a thinking process that involves formulating problems, analyzing, designing, scientific and logical thinking, algorithmic and numerical thinking, recognizing patterns, and developing cooperative and creative thinking. Coding refers to the act of programming or giving instructions to a computer. Coding can be taught through plugged coding, unplugged coding, and, gradually, through communication, the use of landmarks, and robot programming. Coding education demonstrates that digital skills are necessary to support the thinking required in the 21st century.